PSV-9 The effect of warming and drying piglets at birth under cool or warm farrowing room temperatures on post-natal rectal temperatures. (30th November 2020) - Vande Pol, Katherine; Tolosa, Andres; Ellis, Michael; Shull, Caleb M; Brown, Katie; da Silva, Stephan
Abstract: Piglets are born into a relatively cool environment, resulting in body heat loss, especially at low environmental temperatures. Drying and warming reduces this heat loss, but may be less effective at the higher temperatures experienced in farrowing houses in summer. This study compared the effect of warming and drying piglets at birth on post-natal rectal temperature under winter vs. summer conditions. The study was carried out at a commercial facility using a CRD with 96 sows/litters in a 2×3 factorial arrangement of treatments (applied at birth): 1) Piglet Management: Control (no treatment); Warmed (in a heated box for 30 min); Dried+Warmed (dried with desiccant and warmed); 2) Season: Winter (January-March; farrowing room temperature 21.0 ± 1.65°C); Summer (August-September; 25.3 ± 1.67°C). At birth, piglets were weighed; rectal temperature was measured at 0, 10, 20, 30, 45, 60, 120, and 1440 min after birth. Data were analyzed using PROC MIXED of SAS. Litter was the experimental unit; piglet was a subsample of litter. The model included Season, Piglet Management, and the interaction. There were treatment interactions (P < 0.05) for rectal temperatures at all measurement times except at birth. For both Seasons, the Dried+Warmed treatment resulted in greater (P < 0.05) temperatures than Warmed between 20 and 60 min; both treatments had greater (P < 0.05) temperatures than the Control between 10 and 120 min. Rectal temperatures were lower (P < 0.05) in Winter than Summer for the Control and Warmed treatments between 10 and 60 min. However, for the Dried+Warmed treatment, rectal temperatures were similar between Seasons at all times after 10 min. In conclusion, drying and warming piglets at birth was more effective for reducing rectal temperature decline than warming alone and this effect was greater in winter than summer. This research was funded by the National Pork Board.